2015
DOI: 10.1016/j.tjog.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the abortion interval of second trimester pregnancy termination using misoprostol

Abstract: Higher parity, intrauterine fetal demise, and preterm premature rupture of membranes were associated with shorter AI. The regimen of 200 μg oral misoprostol at 6-hour intervals following a 200 μg or 400 μg priming vaginal dose is feasible and efficacious for second trimester pregnancy termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
4
8
0
Order By: Relevance
“…Although previous studies have indicated a correlation between increased interval and CNS abnormalities such as severe hydrocephalus or neural tube defects [25], a recent study by Dickinson did not confirm these associations with the exception of musculoskeletal abnormalities. Similar to the studies by Nesbitt and Giles [25] and Ting et al [26], our results indicate that preterm premature rupture of membranes and CNS abnormalities were associated with a shorter and a longer interval respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous studies have indicated a correlation between increased interval and CNS abnormalities such as severe hydrocephalus or neural tube defects [25], a recent study by Dickinson did not confirm these associations with the exception of musculoskeletal abnormalities. Similar to the studies by Nesbitt and Giles [25] and Ting et al [26], our results indicate that preterm premature rupture of membranes and CNS abnormalities were associated with a shorter and a longer interval respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is important to consider the risk of prolonged duration of labor induction in primiparas, and generate solutions as to how to shorten it. In other reports about second‐trimester abortion, higher parity, the presence of IUFD, lower gestational age, and the presence of premature preterm rupture of membranes were significant factors associated with shorter induction‐to‐delivery time . In our study, IUFD and gestational age were not factors that influenced time to delivery of >24 h. This difference is likely due to study design.…”
Section: Discussionsupporting
confidence: 43%
“…In other reports about second-trimester abortion, higher parity, the presence of IUFD, lower gestational age, and the presence of premature preterm rupture of membranes were significant factors associated with shorter induction-todelivery time. [21][22][23] In our study, IUFD and gestational age were not factors that influenced time to delivery of >24 h. This difference is likely due to study design. We excluded the cases with premature preterm rupture of membranes.…”
Section: Discussionmentioning
confidence: 55%
“…A regimen of 200 mg mifepristone and 800 μg buccal or vaginal misoprostol is 95%-98% effective [19]. Various studies have proven its effectiveness [1,[20][21][22][23][24][25][26] and improved health care system [26] in other setting and attributed the declining complication and mortality rates associated with induced abortions in some LMICs countries especially in Latin America to the widespread use of misoprostol [21,23].…”
Section: Introductionmentioning
confidence: 99%